1982
DOI: 10.1111/j.1365-2923.1982.tb01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate teaching of orthopaedic surgery

Abstract: Orthopaedics is an important component of clinical practice and education in this subject is important. In order to discover how best to teach it a questionnaire was presented to undergraduates at Bristol University at the conclusion of their course. From their replies a course length of 6 weeks with maximum clinical contact, small groups and minimum number of lectures is recommended. Orthopaedic courses nationally have also been analysed and found to rely overmuch upon lectures, to have student group which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Surprisingly, students do not resent examinations. Norris (1982), in a previous sample of undergraduates at Bristol, found that the prospect of an M C Q increased the students' willingness to study. Students have entered medical school as a result of prowess at written examination and are extremely competent candidates.…”
Section: Discussionmentioning
confidence: 92%
“…Surprisingly, students do not resent examinations. Norris (1982), in a previous sample of undergraduates at Bristol, found that the prospect of an M C Q increased the students' willingness to study. Students have entered medical school as a result of prowess at written examination and are extremely competent candidates.…”
Section: Discussionmentioning
confidence: 92%
“…11 The length of the average course is below the six weeks which was recommended by Norris. 12 In addition, such short exposure to a large subject may encourage superficial learning which medical education is specifically trying to avoid. 2,13 One of the main goals of the 'Bone and Joint Decade' is to "influence the training programme in medical schools to include at least six months of exposure to musculoskeletal disorders with the aim of improving the diagnostic skills of general practitioners.…”
Section: The Teaching Of Trauma and Orthopaedic Surgery To The Underg...mentioning
confidence: 99%
“…In the United States (US), 10–18% of primary care consultations relate to musculoskeletal disorders with an annual estimated cost of $850 million (£530, €655) [ 4 ]. Undergraduate musculoskeletal education in the UK is often delivered in combination with other clinical placements and has to compete with other specialities in the curriculum [ 5 ]. The average undergraduate teaching time dedicated to trauma and orthopaedic (T&O) surgery is reported to be around two and a half weeks [ 6 ].…”
Section: Introductionmentioning
confidence: 99%